Relationship between lifestyle and physical development among modern urban adole - Yelizarova, Ye.T.; Gozak, S.V.; Stankevich, T.V.; Parats, A.N. (Environment & Health, 2018)
Objective: We characterized the day activity of the city adolescents taking into account their physical activity.Materials and methods: We estimated the lifestyle of the adolescents with the help of Quantification de l'Activite Physique en Altitude Chez les Enfants adapted by us. Energy expenditures (METdaily) were calculated by The Compendium of Energy Expenditures for Youth. Physical development was assessed after Rorer formula. 247 schoolchildren aged 11-15 years of three cities in Ukraine, not engaged in organized sports teams, took part in the study. Statistical processing was performed with the help of STATISTICA 8.0 package.Results: Connection between an excessive body mass and lifestyle in the adolescents was established. The children with an excessive body mass spend energy more by 8.9% for immobile activity and less by 16.9% for motor activity in comparison with the children with harmonious physical development and reduced body weight (p
Keywords: city adolescents; children of middle school age; immobile lifestyle; physical development